Energy Drive for the Kiruna Mining District Mineral System(s): Insights from U-Pb Zircon Geochronology - Leslie Logan; Joel B. H. Andersson; Martin J. Whitehouse; Olof Martinsson; Tobias E. Bauer (Minerals, 2022)
The Kiruna mining district, Sweden, known for the type locality of Kiruna-type iron oxide–apatite (IOA) deposits, also hosts several Cu-mineralized deposits including iron oxide–copper–gold (IOCG), exhalative stratiform Cu-(Fe-Zn), and structurally controlled to stratabound Cu ± Au. However the relationship between the IOA and Cu-systems has not been contextualized within the regional tectonic evolution. A broader mineral systems approach is taken to assess the timing of energy drive(s) within a regional tectonic framework by conducting U-Pb zircon geochronology on intrusions from areas where Cu-mineralization is spatially proximal. Results unanimously yield U-Pb ages from the early Svecokarelian orogeny (ca. 1923–1867 Ma including age uncertainties), except one sample from the Archean basement (2698 ± 3 Ma), indicating that a distinct thermal drive from magmatic activity was prominent for the early orogenic phase. A weighted average 207Pb/206Pb age of 1877 ± 10 Ma of an iron-oxide-enriched gabbroic pluton overlaps in age with the Kiirunavaara IOA deposit and is suggested as a candidate for contributing mafic signatures to the IOA ore. The results leave the role of a late energy drive (and subsequent late Cu-mineralization and/or remobilization) ambiguous, despite evidence showing a late regional magmatic-style hydrothermal alteration is present in the district.